Influence of highest dominant frequency area on fibrillation dynamics and frequency spectrum on electrograms. (14th October 2021) - Sanchez De La Nava, A M; Rios-Munoz, G R; Gomez-Cid, L; Grigorian-Shamagian, L; Fernandez-Santos, M E; Arenal, A; Atienza, F; Fernandez-Aviles, F
Abstract: Introduction: Highest Dominant Frequency (HDF) has been extensively described as one of the descriptors for Atrial Fibrillation (AF) and some studies also describe the total area activating at this frequency. However, the influence of this area on the registered power spectrum of the electrogram is usually not explained. Objective: To describe the role of the highest Dominant Frequency Area (DFA) on the electrogram signal. Methods: HL1 cell line monolayers were used as AF in vitro model and cultured on p35 plates (N=15) until confluence was reached. Optical mapping was performed to evaluate the electrophysiological activity of the samples employing Ca2+ transient quantification and activation frequency (Hz). Pseudo electrograms were calculated from the recorded signals and their frequency spectrum was evaluated. Results: Two different groups were identified during the study: a group in which the DFA was higher than 0.2% of the total area (hDFA) and a group in which it was lower (lDFA). For hDFA cultures, the ratio between the DF of the catheter and the culture was significantly higher in the hDFA group (0.90±0.18; 0.47±0.13; p-value <0.0001), indicating that more complex scenarios lead to dissociation between the HDF of the tissue and HDF registered on the electrogram. This relation is identified in Figure 1, where the R 2 values for both cases are 0.99 and 0.62 respectively. Figure 2 shows two examples with different DFA and the respective Ca2+ signals, electrograms, and power spectrum density of both signals, exemplifying how lDFA cases can lead to a mismatch between the power spectrum density of the optical mapping signal and the electrogram. Conclusions: Complex arrhythmic scenarios identified as lDFA present a low correlation between the power spectrum registered on the culture and the electrogram, whereas samples in which the DFA is large, the DF from the catheter presents high correlation ratios among both signals, suggesting that clinical scenarios with high variability on the electrophysiological substrate may be difficult to interpret. Funding Acknowledgement: Type of funding sources: Public grant(s) – National budget only. Main funding source(s): Instituto de Salud Carlos III and Ministerio de Ciencia Innovaciόn y Universidades